The Influence of Work Environment, Communication Between Staff, and Motivation on the Performance of Management Staff at Aayan Hotel - Kardianus Manfour; Ronald Suryaputra; Ike Kusdyah (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study aims to analyze the influence of the work environment, communication between staff, and motivation on the performance of management staff at Hotel Aayan, Bali. The study used a quantitative approach with path analysis techniques processed using SmartPLS software version 4.0. The sample in this study was all 40 management staff, spread across five operational villa units of Hotel Aayan. The results of the analysis showed that communication between staff had a positive and significant effect on employee performance with a p-value of 0.040. In contrast, the work environment and motivation variables did not have a significant effect on staff performance because they had p-values ​​of 0.087 and 0.296, respectively. These findings indicate that effective internal communication is a key factor in improving the performance of management staff, while the work environment and motivation have not been statistically proven as the main determinants in the context of this study. The implications of this study emphasize the importance of strategies to strengthen communication between staff in human resource management in the hospitality sector.